Market segmentation for peppers and tomatoes in Africa - Ambali, Mwasilwa; Zohoungbogbo, Herbaud; Ayenan, Mathieu; Eybishitz, Assaf; Barchenger, Derek; Schreinemachers, Pepijn (CGIAR System Organization, 2025)
The agricultural sector is facing a critical gap in data regarding the future preferences and requirements of key stakeholders such as farmers, processors, and consumers, particularly in the context of public-sector vegetable breeding research. While the CGIAR mandate crops benefit from the Seed Product Market Segment Database, vegetables are notably absent, despite their significance for nutrition, health, income, and biodiversity. This brief explains the process used to determine market segments and Target Product Profiles for tomatoes and peppers in Africa through workshops and research conducted by the World Vegetable Center (WorldVeg) in collaboration with the CGIAR Initiative on Market Intelligence. WorldVeg, which develops both finished and nearly-finished breeding lines, conducted a market segmentation exercise for tomatoes and peppers in Africa. This exercise was based on the eight market segmentation criteria with necessary customizations to address the unique characteristics of each vegetable crop. For East and West Africa, the study found 16 tomato segments. Tomato production in East and West Africa is distinguished by altitude, with West Africa featuring lowland cultivation below 300 m and East Africa featuring highland cultivation above 300 m, thus necessitating region-specific disease resistance traits. For hot peppers in East and West Africa, 15 different segments were identified. West Africa prefers habanero peppers, while East Africa’s market is diverse, with chili peppers being the primary crop, along with varying market segments across countries. The market segmentation for tomatoes and peppers provides a foundational understanding of market requirements.